The Relationship Between Language, Culture and Society in Teaching EFL: Islamic Perspective - Athyah Frista; Fathia Zawatha Az-Zahra; Siti Norfita Sari; Zuhudiah Azzahra; Kalayo Hasibuan (Journal of Applied Linguistics, 2026)
This study explores the interwoven relationships among language, culture, and society in the context of English as a Foreign Language (EFL) teaching through an Islamic lens. While previous research has broadly explored cultural integration in EFL, there is a notable research gap regarding how Islamic educational paradigms can be systematically applied to preserve local religious identities amidst globalized English instruction; this study offers a novel integrative model to bridge that gap. It emphasizes how language functions not only as a means of communication but also as a bearer of cultural and social identity. Integrating Islamic values into EFL instruction supports students in maintaining their cultural and religious identities while acquiring English proficiency. The study uses a qualitative descriptive method, drawing on literature and Islamic teachings to propose a culturally and religiously aligned approach to EFL pedagogy. It also identifies key sociolinguistic phenomena such as code-switching, politeness strategies, intercultural sensitivity, and cultural motivation Keywords : Language; Culture, Society; EFL; Islamic Perspective